2015
DOI: 10.2147/opth.s63790
|View full text |Cite
|
Sign up to set email alerts
|

Update and clinical utility of alcaftadine ophthalmic solution 0.25% in the treatment of allergic conjunctivitis

Abstract: Allergic disorders of the ocular surface are primarily characterized as IgE- and/or T-lymphocyte-mediated disorders that affect the cornea, conjunctiva, and eyelid. Approximately 40% of individuals in the developed countries have allergic conjunctivitis, and as such, it is the most common form of ocular allergy. Seasonal allergic conjunctivitis is the most prevalent type of allergic conjunctivitis that impacts the quality of life of patients. This article reviews the pharmacology, pharmacodynamics, pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Antagonists of H 4 R (JNJ7777120, JNJ39758979, INCB38579, and others) reduced pruritus in a number of animal studies [59] as well as itching sensation in different conditions in human patients. Alcaftadine, a topical ophthalmic drug indicated for the prevention of itching associated with allergic conjunctivitis, is a potent H 1 R and H 2 R antagonist (in fact, inverse agonist) with weak inverse agonistic activity also towards H 4 R [60]. Administration of H 1 R/H 4 R antagonists or co-administration of H 1 R and H 4 R antagonists will probably be effective also in humans.…”
Section: Allergic Diseasesmentioning
confidence: 99%
“…Antagonists of H 4 R (JNJ7777120, JNJ39758979, INCB38579, and others) reduced pruritus in a number of animal studies [59] as well as itching sensation in different conditions in human patients. Alcaftadine, a topical ophthalmic drug indicated for the prevention of itching associated with allergic conjunctivitis, is a potent H 1 R and H 2 R antagonist (in fact, inverse agonist) with weak inverse agonistic activity also towards H 4 R [60]. Administration of H 1 R/H 4 R antagonists or co-administration of H 1 R and H 4 R antagonists will probably be effective also in humans.…”
Section: Allergic Diseasesmentioning
confidence: 99%
“…Currently, alcaftadine 0.25% is one of the most prescribed antihistamine agents for allergic conjunctivitis, and is used worldwide [10, 11, 16, 17]. Alcaftadine 0.25% is an H 1 - and H 2 -receptor antagonist [11].…”
Section: Discussionmentioning
confidence: 99%
“…Alcaftadine 0.25% is an H 1 - and H 2 -receptor antagonist [11]. There are some reports of side effects related to alcaftadine 0.25% usage [10, 11, 17], and previous studies reported fewer than 4% of subjects had side effects [12, 13]. Its side effects are usually related to ocular problems such as ocular itching, conjunctival redness, chemosis, lid swelling, and tearing [10, 11, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is that binding of VK to the IgE receptor on surface of the cell conjunctiva can cause the release of the original cytochemical mediator (histamine) and the newly formed mediators (leukotrienes and prostaglandins), and intracellular H1 and H2 in this case bind to each other, resulting in increased permeability of the conjunctival blood vessels in order to trigger an inflammatory response, eventually leading to VK conjunctival vascular congestion, expansion, eye itching and eye tingling and other symptoms (17,18). Olopatadine hydrochloride has a strong inhibitory effect on selective H1 receptor, which can prevent the release of edematous medium from mast cells in blood vessels to directly prevent H1 receptor-induced inflammation phenomenon from inside the cell (19). Houttuynia yellow oil has a very strong bactericidal ability.…”
Section: Discussionmentioning
confidence: 99%